2019
DOI: 10.2147/ppa.s207498
|View full text |Cite
|
Sign up to set email alerts
|

<p>Reliability and validity of the Maltese version of the Perception of Anticoagulant Treatment Questionnaire (PACT-Q)</p>

Abstract: Purpose: Anticoagulant therapy has an impact on the health-related quality of life, as it is a chronic treatment for most clinical indications and also requires some lifestyle changes. Since there was no validated questionnaire available in the Maltese language, the aim of our study was to translate and validate the Perception of Anticoagulant Treatment Questionnaire (PACT-Q2). Patients and methods: The PACT-Q2 explores two dimensions (convenience and anticoagulant treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…In our research project, we decided to translate the DASS and the PACT-Q, because they are both psychometric questionnaires that can be specifically used to assess the quality of life of anticoagulated patients. Therefore, they were administered at the same time to the same patients’ population (results of the validation of the PACT-Q2 are reported elsewhere) 20. The PACT-Q2 is shorter (20 questions to be answered on a 5-point Likert scale), however the items of the two dimensions “convenience” and “treatment satisfaction” have to be scored separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our research project, we decided to translate the DASS and the PACT-Q, because they are both psychometric questionnaires that can be specifically used to assess the quality of life of anticoagulated patients. Therefore, they were administered at the same time to the same patients’ population (results of the validation of the PACT-Q2 are reported elsewhere) 20. The PACT-Q2 is shorter (20 questions to be answered on a 5-point Likert scale), however the items of the two dimensions “convenience” and “treatment satisfaction” have to be scored separately.…”
Section: Discussionmentioning
confidence: 99%
“…The aim of this study was to assess the psychometric properties (reliability and validity) of the Maltese version of the DASS. The psychometric properties of the Maltese version of the PACT-Q have been reported in a separate paper 20…”
Section: Introductionmentioning
confidence: 99%
“…We add to other studies providing evidence that the PACT-Q2 reliably measures patient's perceptions of satisfaction and convenience with respect to their anticoagulation use. 14,[23][24][25]29 As more evidence develops regarding the value of various novel anticoagulant medications, the PACT-Q2 may continue to provide utility in assessing patient perceptions. Our study also has the advantage of including qualitative interviews to further understand the factors underlying convenience and satisfaction ratings in the survey.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 The survey has been used in multiple patient populations to compare specific DOACs and warfarin in patients with AFib. 14,[23][24][25] The PACT-Q2 domain of convenience assesses concern with difficulty taking medication and how bothered the patient is by follow-up submit your manuscript | www.dovepress.com…”
Section: Survey Surveymentioning
confidence: 99%
“…60 136 Improved treatment convenience and satisfaction on the PACT-Q2 scale occurred more often in patients who had switched from VKA to dabigatran than in non-switchers in a 1-year prospective observational study. 55 61 134 137 Coleman et al reported a significant improvement in the Anti-Clot Treatment Scale (ACTS) satisfaction with burden and Open access benefits of OACs scores, 3 months after patients switched from VKA to rivaroxaban. 138 Hanon et al also reported a significant persistent improvement in ACTS burden and benefit scores at baseline, 1, 3 and 6 months postswitch from VKA to rivaroxaban than baseline (burden (46.5, 53.6, 54.9, 54.7, respectively), benefit (10.4, 10.7, 10.9, 10.8, respectively)).…”
Section: Patient-reported Outcomesmentioning
confidence: 99%